2001
DOI: 10.1541/ieejpes1990.121.8_918
|View full text |Cite
|
Sign up to set email alerts
|

Lightning Protection Methods for Customer's Facilities Located in Mountainous Areas Facing The Sea of Japan

Abstract: Surge arresters which installed at customers facilities and distribution lines are often damaged by winter lightning in mountainous areas facing the Sea of Japan. Therefore we have observed the lightning performance at a mountainous area, since 1998, in order to verify the effective lightning protection methods for customer's facilities and distribution lines. Based on the observation data and analysis results using the EMTP, we propose the effective lightning protection methods for customer's facilities.(1) W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…SPDs in window towers are reported to be burned by winter lightnings 6 . In addition, lightning strikes on customers’ equipment (backflow strikes) are accompanied by high energy flowing to distribution lines due to low grounding resistance, and damages to power distribution equipment were confirmed 14 Arresters were observed to burn out due to lightning strikes on blades 15 . Thus, a rise in ground potential is an important issue in the lightning protection design of wind power plants.…”
Section: Protection Coordination Between Cable and Arrestermentioning
confidence: 99%
“…SPDs in window towers are reported to be burned by winter lightnings 6 . In addition, lightning strikes on customers’ equipment (backflow strikes) are accompanied by high energy flowing to distribution lines due to low grounding resistance, and damages to power distribution equipment were confirmed 14 Arresters were observed to burn out due to lightning strikes on blades 15 . Thus, a rise in ground potential is an important issue in the lightning protection design of wind power plants.…”
Section: Protection Coordination Between Cable and Arrestermentioning
confidence: 99%
“…Thus, it became clear that use of overhead ground wires (OGW), including stranded wires, upgrade of discharge capacity of lightning arresters, and other measures improve back flashover protection of high‐voltage distribution lines in winter lightning areas . It was also shown that reduction of grounding resistance in equipment exposed to direct lightning strokes (hilltop loads, wind power generators, and so on) provides efficient protection of high‐voltage distribution lines from back flashover .…”
Section: Introductionmentioning
confidence: 99%